Pengaruh Pemberian Modified Lumbal SNAGS dan MC KENZIE Excercise Terhadap Penurunan Nyeri Pada Low Back Pain Myogenic - Abrar, Muchlas; , Agus Widodo, S.Fis, M.Kes; , Wahyuni, SSt.FT.M.Kes; , Dwi Rosella K, S.St FT., M.Fis (2016)
Lower back pain myogenic is pain around of the lower back mucle or a disorder caused by abnormalities in the muscles of elements without neurological disorders, Low back pain myogenic is a common complaint, and almost everyone has experienced especially in people whose work activities require bending and lifting motion like a farmer. Modality that can be used to treat pain myogenic LBP is modified lumbar snags and excercise Mckenzie, The purpose of research the effect of modified lumbar snags and Mckenzie excercise to decrease pain myogenic LBP. This study uses a quasi experimental design with pre-test and post-test control group design. The experiment was conducted in in villages Sambeng Ngawen Gunung Kidul districts, subjects were farmers who met the criteria established researchers and obtained 16 votes. Decrease in pain was measured with oswestry disability index (ODI) before and after training. data processing and data analysis using SPSS . The effect of using the Wilcoxon test and the test of differences using Mann-Whitney Test. Wilcoxon test results showed that no effect of modified lumbar snags and Mckenzie excercise against a decrease in pain myogenic LBP. Results of Mann-Whitney test showed there was no significant difference between the provision of modified lumbar snags and Mckenzie excercise against a decrease in pain myogenic LBP. With the value of p = 0.710 to P> a. Keywords: modified lumbal SNAGS, Mckenzie excercise, oswestry disability index (ODI).